Explanation of Behavioral Intentions to Mitigate Climate Change with Protection Motivation Theory - Nuran Bayram Arlı; Fırat Demir; Sedat Karakaya; Onur Barca; Furkan Onur Usluer (Journal of Economy Culture and Society)
Climate change, which refers to the radical climatic changes that occur as a result of factors such as the release of various gases into the atmosphere, fossil fuel consumption, and industrial activities, is serious global concern. Food and water shortages, increased flooding, extreme temperatures, new epidemics, and economic losses are all threats posed by climate change. To mitigate the adverse effects of this phenomenon, some measures can be taken by all individuals. The study aims to investigate people’s attitudes toward climate change by determining their behavioral intentions with a model based on Protection Motivation Theory (PMT). The behavioral intentions of individuals to prevent climate change were analyzed with the Structural Equation Model (SEM). The source of data is a questionnaire conducted in Türkiye with 526 people over the age of 18. The results reveal that people’s threat and coping appraisals are effective in the formation of behavioral intentions to combat climate change and thus contribute significantly to protection motivation. Higher response efficiency and self-efficacy lead to higher levels of protection motivation. Threat and coping appraisal account for 65.3% of the total change in behavioral intentions.